1978
DOI: 10.1055/s-0028-1093449
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined Response to Different Ingested Carbohydrates in the Production of Diabetes

Abstract: It has been shown that the metabolic responses to the ingestion of carbohydrates depend upon a) the type of the ingested carbohydrate and b) the genetic build-up of the recipient. In the non-susceptible animal, the ingestion of high sucrose, fructose or glucose diets will ensue in "normal" metabolic responses. In the susceptible animal the ingestion of these same carbohydrates will result in impairment of the carbohydrate and lipid metabolism, which will ultimately lead to the development of diabetes and diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Diabetes in this model has many features in common with human, non-insulin dependent diabetes (21). The rats were genetically selected from the Hebrew University albino rat strain for their genetic propensity to develop impaired carbohydrate metabolism when fed a copper-poor high-sucrose diet.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes in this model has many features in common with human, non-insulin dependent diabetes (21). The rats were genetically selected from the Hebrew University albino rat strain for their genetic propensity to develop impaired carbohydrate metabolism when fed a copper-poor high-sucrose diet.…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged administration of either a high fructose or sucrose diet to genetically selected rats induces a metabolic syndrome characterised by insulin resistance and decreased glucose tolerance, as well as increased plasma triglyceride and cholesterol levels (Cohen et al 1977, Cohen 1978. We have previously reported that administration of a sucrose-rich diet (SRD) to normal rats for 6 months induced such metabolic abnormalities, together with a significant increase in both pancreatic islet number and -cell area (Lombardo et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…he Cohen diabetic rat is an exceptional genetically derived experimental model of dietinduced type 2 diabetes that reproduces many features of the disease in humans (1)(2)(3)(4)(5). This rodent model stands out among other experimental models of type 2 diabetes in several important ways.…”
mentioning
confidence: 99%
“…This rodent model stands out among other experimental models of type 2 diabetes in several important ways. Its most outstanding and distinctive feature is that it expresses genetic susceptibility (sensitivity and resistance) to a carbohydrate-rich diet, a central feature of type 2 diabetes in humans (1,2,4,5) that is not present in other major genetically inbred rat strains that simulate type 2 diabetes in humans. The other major rat models of type 2 diabetes, the Goto-Kakizaki (GK) (6,7), the Otsuka Long-Evens Tokushima Fatty (OLETF) (8 -10), and the Zucker diabetic fatty (ZDF) rats (11,12) develop diabetes spontaneously, without any important relationship to the composition of diet.…”
mentioning
confidence: 99%